EVALUASI EFEKTIFITAS JEMBATAN PENYEBERANGAN ORANG (JPO) DI KOTA SAMARINDA - SAHRIANTO, FAJAR (KURVA S JURNAL MAHASISWA, 2018)
in planning the transportation of one of the elements of traffic that needs serious attention is pedestrians. Infrastructure for pedestrians who fulfill security, safety, comfort and are able to minimize delays or traffic accidents while crossing are definitely very needed supporting facilities such as pedestrian bridges. This study aims to determine the effectiveness of pedestrian bridges for pedestrians. This research was conducted in July 2018, located at S. Parman street, Gajah Mada street, Ir. H. Juanda street, Slamet Riyadi street, Samarinda city, East Kalimantan Province. This research uses primary data collection methods, namely, by direct survey through the distribution of questionnaires and secondary data by collecting location data. The analysis used in this study is Guttman Scale or also called scale analysis and crossing time analysis, analysis of determination of crossing facilities. The results of the evaluation of this study indicate that based on the analysis of the crossing time of the value of R on S. Parman street 4.2. Gajah Mada street 8.5. Ir. H. Juanda street 5.43. Slamet Riyadi street 2.8. In all four locations the pedestrian bridge can be said to be the longest route, and the analysis of the determination of the fourth crossing facility of the JPO recommendation is pelican with a waiting stall. Based on Guttman's analysis on S. Parman street 59% (criteria are quite effective), Gajah Mada street is 38% (ineffective criteria), Ir. H. Juanda street 63,2% (effective criteria), Slamet Riyadi street 83% (very effective criteria), JPO cannot be used optimally for people with disabilities because there is no accessibility facility especially for wheelchair users.